Analysis of Mathematical Problem Solving Ability in View fromSelf-Efficacy Student Social Arithmetic Material - Agustina, Nia; Hayati, Laila; Kurniati, Nani; Kurniawan, Eka (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2023)
This qualitative descriptive research aims to describe students' mathematical problem solving abilities based on Polya indicators in solving social arithmetic problems in terms of self-efficacy. The research subjects were 4 students in class VII of SMP Negeri 4 Gunung Sari for the 2022/2023 academic year, consisting of 2 students in the high category and 2 students in the low category. Data collection techniques using questionnaires, tests and interviews. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this research were obtained from (i) students with level self-efficacy high have high mathematical problem solving abilities can go through all stages of problem solving abilities, namely understanding the problem, preparing a plan, implementing the plan, and checking again. (ii) students by level self-efficacy Low students have low mathematical problem solving abilities which can also be seen from the results of students' work through only two stages, namely the stage of understanding the problem and implementing the plan. With suggestions for students who are at each category level self-efficacy and the level of mathematical problem solving abilities, it is hoped that they can further maximize their abilities